Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 1260631306 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1260631306 records from 19612 constituent datasets: 1340 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 260 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 115 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 371 records from orthopteracollections-nhmj-ioj. 778 records from Bird specimens of Saitama Museum of Natural History. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 22662 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 2226 records from pyrosequencing Raw sequence reads of deep-sea Archaea. 256 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 1013 records from flower availability 2008 Alb-korrigiert. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 13 records from Dinoflagellate abundance of Hole 14-144. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 70 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 346 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 4902 records from Macrobenthos Chukchi Sea, 1986. 2 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 208 records from Condamine Alliance. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 18 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 11032 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 367 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 170 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 107 records from Faunal assemblage of sediment core TR149-31. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 34728 records from Microbial community in marine sediments. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 43 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 204 records from Planktic foraminifera abundance of Hole 29-284A. 73 records from Planktic foraminifera abundance of Hole 49-409. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 7283 records from Colecção Entomológica IIA. 13404 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 33526 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 42 records from Nannofossil abundance of Hole 10-91. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 996 records from DMNS Egg Collection (Arctos). 2538 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 13203 records from Lepidopterous specimens of Yamagata Prefectural Museum. 1324 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 262 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 14 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5462 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 45970 records from Herbarium Universitatis Daugavpiliensis. 592 records from Colección de Entomología - Curculionidae. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 2208 records from marine sediment metagenome Raw sequence reads. 26 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 393 records from Dinoflagellate cyst counts on sediment core ABC26. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 44312 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 971 records from azorean_vascular plants. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1903 records from Plecoptera. 10 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 23660 records from Swan Coastal Plain Survey. 18 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 184 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 14 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 62116 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 132 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 20 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 383 records from Neogene palynomorpha from site 81-552. 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 184 records from Protozoa Abundance_Microbial Parameters. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 32 records from Antarctic Pycnogonids II. 10 records from Oberservation of birds at station PS14/143 along 49° West. 5120 records from Upper Silesian Museum, Bird Observations. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 1628 records from Données naturalistes de Quentin ROME. 4 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 46 records from Relative abundance of coccosphere-units at site GIK23414. 4 records from Planktic foraminifera abundance of Hole 19-191A. 44104 records from CNIN/Abejas de México/Apoidea. 113 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 3569 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 828 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1768 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 12 records from Ostracod species in Oligocene sediments of core CRP-3. 14 records from Nannofossil abundance of Hole 10-93. 3 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 12 records from Art´n Vielfalt im Kinderwald. 52 records from Planktic foraminifera counts of sediment core V14-77. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 3800 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 4 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 294 records from Invasive Non-Native Species, Outer Hebrides. 13 records from Benthic macrofauna abundance of sediment core 13077-093. 1436 records from Naturalis Biodiversity Center (NL) - Crustacea. 120 records from Amphibian and Reptilian (KIEE-AR). 21 records from Brown algae specimens of Komatsu City Museum. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 242 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 2046 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 686 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 465 records from The Broward College Insect Collection. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 14 records from Berea College, Ralph L. Thompson Herbarium. 94 records from Distribution of nanoplankton at trap WR2. 1406 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 13624 records from Ecosphère_2017_12_18. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 151854 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 794 records from Isle of Wight non-native invasive species. 3 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 581 records from Floristic records in the Moscow and Novgorod regions. 17 records from Marine metagenome ICM_AGW. 1632 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 61 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 60 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 50 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 735 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 81 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 7 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 68 records from Streuobstwiese. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 816694 records from Western Australian Museum provider for OZCAM. 1152 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 26 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 2780907 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 10 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 33 records from Waldstück am Schullandheim Bad Bederkesa. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1461 records from M. Gollop Collection. 1 records from Données naturalistes d'Olivier DELZONS. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 7 records from Analyses of the recent components of sediment core PS1277-1. 352 records from Nannofossil abundance of Hole 60-458. 6920 records from MEXU/Leguminosae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 151 records from Planktic foraminifera counts of sediment core RC08-49. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 227 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 6192 records from marine sediment metagenome Metagenome. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 3769 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 371 records from Bannwald Burghauser Forst. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 12496 records from SEWBReC Bees, Wasps and Ants (South East Wales). 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 308 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 111 records from Total foraminifera counts of multinet M33/1_MSN1029. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 20520 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 91 records from Artenvielfalt des "Grünen Klassenzimmers". 250 records from Museu de Ciències Naturals de Barcelona: BGJBB. 91 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 174 records from BIRDRACE Bon(n)apartemöwen. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1545 records from NatureMap Calcrete Survey. 452 records from Benthic foraminifera counts of sediment core PS1852-2. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 5 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 46782 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 412 records from Heinersdorfer Sumpfwiese. 279489 records from ARABEL - Arachnologia Belgica. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 22680 records from Arctic Species Trend Index (ASTI) : Marine. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3332 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 33416 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 553 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 61009 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 17755 records from K-State Museum of Entomological and Prairie Arthropod Research. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 13 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 277 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 1825 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 946 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 124900 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 2 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 1036 records from BUND - Dassower See (Lübeck/Dassow). 8 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 346 records from Birds and plant species near Petushki town (Vladimir region). 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 2006 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 557 records from Cuxhavener Küstenheiden. 40 records from Planktic foraminifera abundance of Hole 14-137. 2311 records from UWYMV Bird Collection (Arctos). 1985144 records from Hatikka Observation Database. 62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 97895 records from inatura - Erlebnis Naturschau Dornbirn. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 386 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 32 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 3792 records from Sea water microorganisms Raw sequence reads. 1417876 records from PlutoF platform observations. 1500 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 655 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 10 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 7 records from Benthic macrofauna abundance of sediment core 13078-015. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5528 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 39 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 161 records from Nannofossil abundance of Hole 30-285A. 213 records from Pollen record of profile 3TZ. 200 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 362385 records from South Australian Museum Australia provider for OZCAM. 3 records from A new species of forest-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from the Indawgyi Wildlife Sanctuary, Kachin State, Myanmar. 21 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 4 records from Coccolith counts of multinet M32/5_MSN981. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 7115 records from Whicher Scarp Flora Survey. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6446 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 129 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 20 records from Occurrence of mammalia relicts at site Niederlehme. 2366 records from Cryoconite sediments Targeted Locus (Loci). 172 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 75961 records from Tasmanian Museum and Art Gallery provider for OZCAM. 3203 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 938 records from TTRS Mammals. 148 records from Occurrence of mammalia relicts at site Veternica. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4579 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 33 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 2076 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 47 records from Nannofossil abundance of Hole 9-79. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 159516 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 3189 records from National Museum of Natural Science. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 111 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 7 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 6158 records from Marine metagenome ICM_JRV. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 21400 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 131252 records from Norwegian Lepidoptera working group. 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 308 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6192 records from NE Scotland fish records 1800-2010. 301 records from Marine sediment metagenome ICM_GMS. 48 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 648 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 1014 records from Pollen profile ADR353. 97 records from Foraminifera species abundances from tow TT011_7-MOC66. 6 records from Sächsische Schweiz (Pfaffenstein). 23888 records from Données ONEMA BDMAP 2014. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 115 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 7609 records from Amundsen Gulf Overwintering Eukaryote Community. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 84 records from Roter Berg Werdau (Leubnitz). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 2 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 22015 records from University of California Santa Barbara Invertebrate Zoology Collection. 570 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 165 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 673 records from Planktic foraminifera abundance of Hole 45-395. 14879 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 40052 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 9 records from Herbarium specimens of Limoges university (LIMO). 3750 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 10082 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 112 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 3823 records from UTEP Invertebrates (Arctos). 59 records from Schulteich Freie Waldorfschule Darmstadt. 2988 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 12 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 3162 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 1872 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 36 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 63 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 19 records from Marine metagenome ICM_CNE. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 128 records from Faunal assemblage of sediment core TR149-32. 831 records from Nannofossil abundance of Hole 15-149. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 6 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 3155 records from Registros Primates Neotropicales Convocatoria APC. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 134 records from Pollen record of profile 3TZ2. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 8 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 143 records from Dermaptera in the icipe collection. 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 29 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 1509 records from The national database for marine data (MADS). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 26 records from Nannofossil abundance of Hole 9-82. 204 records from Foraminifera abundance of Hole 57-440A. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 6 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 6 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 153 records from Planktic foraminifera abundance of Hole 18-181. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 88102 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 337 records from Pollen data of trap CB4. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 1 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 16 records from Valentin Moser Bats. 807 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 104886 records from Extracellular DNA marine sediment Targeted Locus (Loci). 54 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 285 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 376 records from "Schwarzwassertal" bei Pobershau. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2340 records from marine metagenome Targeted Locus (Loci). 24493 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 155 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 3 records from Occurrence of mammalia relicts at site Igstadt I. 268 records from Planktic foraminifera abundance of Hole 22-217. 304444 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 975 records from Danielsberg (Mölltal, Kärnten). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 8 records from Nannofossil abundance of Hole 39-353A. 16985 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 3877 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 118 records from Nannofossil abundance of Hole 3-15. 1887 records from Foreign plant germplasm collections in Ghana. 1558 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 328 records from UCYN-A diversity in the Pacific. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 186 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 13637 records from Collection Pisces SMF. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 1 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 2195 records from MEXU/Tipos de plantas vasculares. 30 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 41 records from MSUM Ichthyology and Herpetology Collections. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 136 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 15 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 31014 records from River Biologists' Database (EPA). 154146 records from CABI Africa Invasive and Alien Species data. 7504 records from Eurobodalla Regional Botanic Gardens. 1650 records from Great Eastern Ranges - Slopes to Summit. 150 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 75 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 191294 records from Tiroler Landesmuseum Ferdinandeum. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 1031 records from Données supplémentaires Atlas des Mammifères marins. 18 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 34332 records from Protist Diversity in the East China Sea. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1715185 records from NBIS Records to December 2016. 149 records from Abundance of radiolaria at station UT99-23-2. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2676 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 378 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 17 records from Ostracoda abundance of Hole 24-238. 17 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 9 records from Meiofauna abundance in sediment core 54301-010. 870 records from Marine metagenome ICM_AWP. 151 records from Collection Hydrozoa - ZSM München. 3583 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 9057 records from NE Scotland other invertebrate records 1800-2010. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 21 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 7 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 558 records from Foraminifera abundance of Hole 74-526A. 267 records from Dinoflagellate abundance of Hole 81-555. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 60 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 2 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4987 records from EDIT - ATBI in Gemer area (Slovakia). 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22113 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 181 records from Nannofossil abundance of Hole 27-259. 66 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 152 records from AKG-Gelände (Bensheim). 237 records from Planktic foraminifera abundance of Hole 21-207. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 23 records from Benthic foraminifera abundance of Hole 93-603. 1 records from Occurrence of mammalia relicts at site Raagelund. 6 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 48 records from Ostracoda abundance of Hole 48-403. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1121 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 20004 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 188 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 478 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 163 records from Planktic foraminifera counts of sediment core V27-178. 243 records from Antarctic Amphipoda. 210 records from Lebensraum Gesamtschule (Langerwehe). 373 records from Foraminifera abundance of Hole 64-481. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 905 records from Coléoptères Silphidés du département du Loiret. 4540 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 2300 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 31152 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 384 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 399 records from Planktic foraminifera abundance of Hole 14-142. 39329 records from Insects, Outer Hebrides. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 18 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 219 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 309 records from Echinoderms from the Seaflower Biosphere Reserve. 280 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 194 records from Nannofossil abundance of Hole 49-408. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 11 records from Analyses of the recent components of sediment core PS1011-1. 140923 records from Allan Herbarium (CHR). 54486 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 24 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 323 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 6 records from Foraminifera abundance of Hole 58-442. 7264 records from Uncultured eukaryotes Targeted Locus (Loci). 253 records from Données naturalistes d'Olivier LAURENT. 407 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 98 records from Warnowtal (Rostock). 930 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 1302 records from Marie-Victorin Herbarium (MT) - Bryophytes. 462 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 2 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 202122 records from National Benthic Inventory. 16 records from Phenological Center - Fishes (Murmansk). 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 15 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from BIRDRACE Die Wendehälse. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 8332 records from Scotland Otter Survey Database. 4 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1652 records from Utah State University, Intermountain Herbarium. 351600 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 19 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 61269 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 6085 records from Naturalis Biodiversity Center (NL) - Pisces. 216664 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 480 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 550 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 321633 records from Seasearch Marine Surveys in England. 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 38 records from Planktic foraminifera abundance of Hole 84-566C. 2963 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 95 records from Nannofossil abundance of Hole 1-3. 132 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 255 records from Occurrence of mammalia relicts at site Raj Cave. 91 records from Nannofossil abundance of Hole 6-55. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 98342 records from Arizona State University Hasbrouck Insect Collection. 3776 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 39 records from Planktic foraminifera abundance of Hole 27-260. 2536 records from Invasive Alien Species Occurrence in Ghana. 126728 records from CCAMLR historic KRILL. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 412 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1053 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 87901 records from MDFRC macroinvertebrate survey. 62 records from Amtsrain Apolda-Zottelstedt. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 179 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 80584 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 25 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 57 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 104 records from Nannofossil abundance of Hole 31-299. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 110 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 98 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 2 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 122 records from Shrews of Poland. 152 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 8 records from Nannofossil abundance of Hole 2-11. 5 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 28 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 166 records from Wiese am Waldrand (Gurtweil). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 311 records from UWYMV Herpetology Collection (Arctos). 28138 records from Midden-Limburg Fish Ponds Survey. 63102 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 12956 records from National System of Protected Areas in Poland - Animals. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 240 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 158 records from Planktic foraminifera counts at CTD station PS55/063. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 4193 records from Leicestershire and Rutland Aculeate Records. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 10110 records from Suivi Temporel des Libellules (STELI). 1854519 records from First Bird Atlas. 1315 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 5305 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 46337 records from University of Ghana - Ghana Herbarium. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1911 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 21788 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2807 records from Natura 2000 Vallée de la Seille. 591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 10192 records from Inventario de Hymenóptera; parasítica en México. 19066 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 126170 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 3 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 1798 records from 3Soil16S. 1187 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 67 records from Planktic foraminifera abundance of Hole 9-76. 752 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 76 records from BIRDRACE Nachtigallen. 63 records from Nannofossil abundance of Hole 24-233A. 3148 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 55 records from Dinoflagellate abundance of Hole 28-274. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 824 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 23138 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 79 records from Planktic foraminifera counts of sediment core A15-558. 276 records from Birds Specimens of Akita Prefectural Museum. 6 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 442 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 84 records from Total foraminifera counts from M35/1_MSN1051. 8 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 4 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 1952 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2098 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 285620 records from Estonian Nature Observations Database. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 5 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1178 records from Birds (NMNO-BI). 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 770 records from Nivå Bay species list, Zealand, Denmark. 814 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 19758 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 14 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 2 records from Planktic foraminifera counts of multinet PS2616-5. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 8414 records from CASES2003_2004. 39582 records from Fife Nature Records Centre combined dataset. 57 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 23 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) — three possibly threatened Brazilian species. 10 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 822 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 144 records from BIRDRACE Niederlausitz-Team. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 1441 records from Planktic foraminifera abundance of Hole 18-173. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 279 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 3793 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 123 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 22 records from Collection Ephemeroptera - SMF. 33 records from Microzooplankton abundance and biomass at station TT045_15-2. 10397 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 15787 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 14557 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 16506 records from Database for alien invasive plants occurrences in Germany. 36 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 83 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 84 records from Benthic foraminifera abundance of Hole 84-566C. 704 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 7345 records from Spider (NSMK-SP). 2131 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 57217 records from National Biodiversity Data Bank. Observation records, 1900-2014. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 200 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 22 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 92 records from Nottekanal, Klasse 7 - 10. 54 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 103 records from Percentages of planktonic foraminifera species in sediment core V30-40. 277 records from Nannofossil abundance of Hole 37-333. 4845 records from Inventaire des Mollusques Sphaeriidae de France. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 78 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1409 records from Diatom assamblage in samples from sediment trap OG5. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 50 records from Flora und Fauna im Brexbachtal. 899025 records from MICROBIS database. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3399 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 248680 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 30091 records from BIOWIDE eDNA Fungi dataset. 45186 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 59 records from Nannofossil abundance of Hole 73-521A. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1739 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 31457 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 124 records from Kirkliston Range stream monitoring. 10 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 21222 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 733 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 2 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1092 records from Nannofossil abundance of Hole 82-558A. 26 records from Planktic foraminifera counts of sediment core RC13-154. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 21 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 89649 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 624930 records from SEWBReC Birds (South East Wales). 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 807 records from Área Galeras - Monitoreo de Aves, 2016. 141 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 455 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 11260 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 782 records from Planktic foraminifera abundance of Hole 42-372. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 29087 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3214 records from MEXU/Flora de Oaxaca. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 19486 records from marine sediment metagenome Raw sequence reads. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 40 records from Heavy minerals of sediment core PL94-64. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 28064 records from Amphibiens et Reptiles de France (Enquête 2). 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 6303 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 132 records from (Table 6) Ostracod assemblages of sediment core 9409. 368 records from Ring ouzel national sample survey in the UK in 1999. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 215 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14846 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 638313 records from Données de la flore d’Alsace (SBA). 233 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4352 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 42 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1127 records from Nannofossil abundance of Hole 17-167. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 8 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 3817 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 119 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 109 records from Planktic foraminifera counts of sediment core V04-8. 126 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 7 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4644 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 9313 records from MfN - Fossil plants (Paleophytic). 4227 records from Données naturalistes de Loïc SALAUN. 16 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 15045 records from EAC - Herbário Prisco Bezerra. 1 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 2507 records from East Ayrshire Species Database. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 9 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 135 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 9275 records from Collection Crustacea - ZMB. 935 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 36 records from Nannofossil abundance of Hole 25-249. 28 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 4536 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 594 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 572 records from NEW-1. 4 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 38 records from Was lebt in der Brutzwiese?. 61 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 28 records from Biodiversity Surveys, South-east Arnhem Land. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 2 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 78 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 120 records from Tejidos asociados al estado de conservación y riesgo de extinción del ensamblaje de anfibios de tres páramos colombianos. 5809 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 60 records from Wichita State University Collection. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 302 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 8158 records from Dark ocean microbial diversity. 1 records from Benthic foraminifera abundance of Hole 96-624. 986 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 10 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 30736 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2621 records from Fungi specimens of Saitama Museum of Natural History. 1543 records from Pollen record of sediment core Bokanjacko Blato 1. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 36 records from BIOMEO_2017_12_18. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 841 records from Planktic foraminifera abundance of Hole 72-518. 1036 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 22 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 6 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 28307 records from Bosque Mesófilo de Montaña de México. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 22853 records from Données de Lépidoptères de Denis Vandromme. 20764 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 29 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 3884 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 46 records from Mammal specimens of Komatsu City Museum. 12 records from Urban Barcode Project - Fungi. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 270 records from ACT and Southern Tablelands Weed Spotter. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 41 records from Örtzemündung (Stedden). 1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 30233 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 2931018 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 38 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1475 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 3262 records from Natural History Museum Rotterdam (NL) - Chordata collection. 39 records from Occurrence of mammalia relicts at site Sütto_6. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 4 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 6835 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 6 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 23 records from Ackerrain Plönhagen. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 242 records from Malawi-Histeridae-Biodiversity-Data. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1438 records from Planktic foraminifera abundance of Hole 7-64. 6588 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 1078 records from Pollen profile from Seminary School Basin. 25 records from Microzooplankton abundance and biomass at station TT043_4-1. 52 records from Benthic foraminifera and algae abundance of Hole 35-325. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 165 records from BIRDRACE Gätkes Erben. 2990 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 103 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 15850 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1882 records from Carabidae of the European North-East of Russia. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 52 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 524 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 6 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 3 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 4880 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 88 records from Total foraminifera counts from M35/1_MSN1065. 2781 records from Marine Turtles. 196 records from Foraminifera abundance of Hole 33-317A. 658 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 6 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 6 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 156 records from Nannofossil abundance of Hole 67-499B. 463 records from Foraminifera abundance of sediment core IN68-9. 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 6661 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 10766 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 4230 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 42 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 1625 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1208 records from Microbial diversity studies of Arabian Sea sediment. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14256 records from La familia Asclepiadaceae en México. 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 311 records from Benthic foraminifera abundance of Hole 41-366A. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 746 records from Otter survey of Ireland 2004 & 2005. 2112 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 9968 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 10 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 144 records from Total foraminifera counts of multinet POS247/2_MSN1386. 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 1854 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 23 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 9781 records from CSIRO, fish surveys by the Soela, 1980s. 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 61 records from Alien Species in Poland - Plants. 905 records from Microfossil abundance of Hole 16-158. 385 records from Nannofossil abundance of Hole 78-543. 22771 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1156 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 26 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 8423 records from University Of Pretoria: Lacewing Database Project (1911-2015). 140 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 382 records from Nannofossil abundance of Hole 66-490. 195 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 2 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3350 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 11305 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 6 records from Abundance of benthos infauna at station GIK23065-1. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1618 records from uncultured eukaryote Raw sequence reads. 2 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 515 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 3454671 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 228 records from Bishop's University Insect Collection (BUIC). 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 25 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 5350 records from Sediment metagenome. 570320 records from BioFokus. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 9643 records from Anymals+plants - Citizen Science Data. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 3383 records from Planktic foraminifera abundance of Hole 23-219. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 849 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 96 records from Total foraminifera counts of multinet M26/1_MSN845. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 68 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 32 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 725075 records from Finnish Floristic Database (Literature Sources). 7 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 2425 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 6 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 11409814 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 16 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 175 records from Nannofossil abundance of Hole 41-366A. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 192 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 1820 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 507 records from Planktic foraminifera abundance of Hole 84-567A. 127 records from Nannofossil abundance of Hole 39-359. 1857 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 30 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 140 records from Nannofossil abundance of Hole 49-412. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 26 records from Abundance of benthos infauna at station PS1240-1. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 994 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 20 records from Nannofossil abundance of Hole 3-22. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 477 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1305 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 8190 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 134 records from BIRDRACE Griffin Wood Warblers. 140 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 9 records from Planktic foraminifera abundance of Hole 94-611B. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 864 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 911 records from Nannofossil abundance of Hole 30-286. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 5 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 38 records from Nannofossil abundance of Hole 7-63. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 77563 records from University of Tennessee Bryophyte Herbarium. 5324 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 26 records from Planktic foraminifera counts of sediment core V28-128. 15272 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 44348 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 16924 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 6541 records from Likona Invertebrates. 291 records from SuLaMa reptile survey 2013. 309 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 129368 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 140 records from Nannofossil abundance of Hole 7-62A. 3379 records from Amphibiens de Guyane. 182 records from Planktic foraminifera abundance of Hole 62-465. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 30 records from Nannofossil abundance of Hole 9-82. 1186 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 7 records from Collection Myriapoda - SNSD. 2 records from BB-Biodiversität a. 7248 records from DBRC Hemiptera species records 1969 to 2015. 3714 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 106 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 41 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from DD_cyano Targeted loci environmental. 4 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 96 records from Coleção de Nematoda do Museu Nacional - UFRJ. 6652 records from Inventory of plant species through Benin (West Africa). 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1778 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1868 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3546 records from Dorset SW Pilot species dataset. 8 records from Benthic macrofauna abundance of sediment core 13077-087. 2904 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 324 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 302 records from Nannofossil abundance of Hole 24-237. 2080 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 13845 records from Cumbria Non Native Invasive Species. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 596 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 94 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 1056 records from Diatom assamblage in samples from sediment trap OG4. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 359 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 76096 records from England Non Native Species records 1965 to 2017. 1 records from A second contender for “world’s smallest fly” (Diptera: Phoridae). 5 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 6 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 1988 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 107 records from Total foraminifera counts from multinet M31/2_MSN890. 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 422 records from Collembola of the Chernaya river basin. 45 records from Estimated plankton abundance at station PS63/064-6. 4 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 28924 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 7 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 79 records from Foraminifera abundance of sediment core C1960.201. 505 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 527 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 36280 records from EDP Foz Tua: Bat Roosts - Ecologial & Compensatory Measures Monitoring Programs [2011-2017]. 795 records from Benthic foraminifera abundance of Hole 84-570. 1091 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 24 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 102 records from Colección de Zoología Invertebrados - Helmintología. 918 records from IASTracker. Invasive Alien Species database. 159 records from Planktic foraminifera assemblage in sediment core SU90-I06. 179524 records from Ornitho.eus. 188260 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 25487 records from fishes_inep_and_nfh. 89 records from Total foraminifera counts of multinet POS247/2_MSN1384. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 254 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 54 records from Planktic foraminifera counts of sediment core V16-20. 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 15 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 78 records from Naturpark Kottenforst-Ville 19.6.09. 1 records from Systematics of Guajirolus ektrapeloglossa Flowers 1985 (Ephemeroptera: Baetidae). 49119 records from Marine Water Column Samples Targeted loci environmental. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 795 records from UCBG TAPIR Provider. 133 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 18 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 371 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 326 records from MUFAL herbarium - Museu de História Natural da Universidade Federal de Alagoas - Herbário Virtual REFLORA. 333 records from renaturierter Main (Kemmern bei Bamberg). 139 records from Montana State University - Billings. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 890 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 665 records from Geochemistry and sedimentology on core POS200/10_28-1. 533 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 452106 records from Oskarshamn herbarium (OHN). 1 records from Synthèse de la Répartition des populations de chamois en 2006 (réseau Ongulés sauvages ONCFS-FNC-FDC). 277 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 158 records from Michael Barkla's Observations. 9446 records from Batsites inventory for England (1949-2011). 5340 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 297 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 93 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 195 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 36 records from Planktic foraminifera counts of sediment core RC14-7. 1 records from A New Genus and Species of Clingfish (Teleostei: Gobiesocidae) from Western Australia. 2849 records from Algae collection. 72 records from Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions. 9269 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 7 records from Nannofossil abundance of Hole 6-49. 53 records from Chronicle of Nature - Phenology of Mammals of Tigirek State Nature Reserve. 4470 records from Données naturalistes de Jean-Paul LECHAPT. 55 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 5061 records from Metagenome from mudbank Area,Alappuzha Kerala India. 68 records from Planktic foraminifera abundance of Hole 16-161. 4347 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 952 records from Guinea-Bissau Herpetological Collection - IICT. 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 78 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 5 records from Planktic foraminifera abundance of Hole 19-184B. 2 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 10786 records from Camera trapping bird data. 39 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 13 records from Planktic foraminifera counts of sediment core V27-47. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2044 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 3287 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 385 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 120 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 46 records from AlgaTerraMovies. 266 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 364 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 458 records from Percentages of planktonic foraminifera species in sediment core V15-168. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 88 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 8 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 110 records from Nannofossil abundance of Hole 20-200. 907 records from Pollen profile Märchenwald B, Harz, Germany. 243 records from Thistles species and abundance. 61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 2851 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 15 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 252 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 57 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 753755 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 854 records from flower availability 2008 Hainich. 1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 1125 records from Données naturalistes de Stéphane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 10811 records from Andes to Amazon Biodiversity Program. 155300 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 444 records from Collection Echinodermata - ZMB. 1 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 244 records from WildesMoor bei Schwabstedt. 870 records from Inventario herpetofaunístico del noroeste de Hidalgo. 388 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 707 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 14 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 380 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 13 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2772 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 751 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 562 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 128 records from Planktic foraminifera abundance of Hole 94-611. 168 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 3 records from Abundance of zooplankton in the Aral Sea. 210 records from Fish Fauna of Berlin. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 1432 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 2004 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 1968320 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 105 records from Total foraminifera counts of trap L2_92_A42. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 1170 records from Département_du_Var_2017_12_18. 191 records from sediment microorganism Metagenome. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 127 records from Wildlife Observations Bardon Hill 31.5.09. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 69 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 6 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 1533 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 3455 records from permafrost metagenome Targeted loci environmental. 44920 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 3139 records from CTD water column metabarcoding. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 1741 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 28 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 221 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 20161 records from Hydrate Ridge, OR - Deep sea cold seep ecosystem Targeted Locus (Loci). 330 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 13 records from Benthic macrofauna abundance of sediment core 13200-047. 18 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 54 records from synthese_Protistdiversity_KG. 6279 records from SPC CoFish Fish Observations Palau 2007. 68952 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 101 records from Planktic foraminifera abundance of Hole 28-265. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 101 records from Benthic foraminifera abundance of Hole 42-372. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 469920 records from Natural England Marine Monitoring surveys. 756 records from Range table from benthic foraminifers in ODP Hole 139-857A. 148 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 3 records from Taxonomic revision of the genus Tarmia Lindsey, 1925 stat. rev. (Hesperiidae: Hesperiinae: Hesperiini: Moncina) with the description of a new species from the Andes. 356 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 3 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 34 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 12 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 122 records from Foraminifera species abundances from tow TT011_10-MOC71. 14 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 2171 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 4083 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 111802 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 5 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 3072 records from marine sediment metagenome Metagenome. 1169 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 4 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 638 records from Benthic foraminifera abundance of Hole 56-435. 2 records from Microzooplankton abundance and biomass at station TT054_21-15. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 11251 records from Données naturalistes de Pierre FRAPA. 1035 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 2 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 97 records from Collection Crustacea ZMG. 85 records from Naturpark Kottenforst-Ville 16.6.09. 12 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 749 records from Planktic foraminifera abundance of Hole 15-154A. 661 records from Données de l'enquête Escargots de l'ONEM (onem-france.org). 146 records from Tortugas marinas de la Isla Cayos de Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 88 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 12 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 118 records from Natur aus zweiter Hand am Muldestausee. 176 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 253862 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 190 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 23 records from TBW-Schafberg. 4952 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 81 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 1714 records from HPL - Herbário do Jardim Botânico Plantarum. 1020 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 35 records from Benthic foraminifera abundance of Hole 42-381. 1159750 records from Amplicon sequencing of Tara Oceans DNA samples corresponding to size fractions for protists.. 36 records from Total foraminifera counts of multinet M42/3_MSN1368. 2801 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 123527 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 2 records from Synthèse de la répartition des populations de cerf élaphe en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 9424 records from Données naturalistes (Rhopalocères et Zygènes) de Sébastien LABATUT (indépendant). 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 2466 records from TTRS Ornithology. 313 records from Stadtpark Herzberg (Elster). 29 records from Nannofossil abundance of Hole 29-280. 131 records from Unser Schulhof - eine Apotheke. 1 records from Chance, luck and a fortunate finding: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes: Xenodontinae), from the Brazilian Pantanal wetlands. 54 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 37 records from Berlin - Treptower Park / Karpfenteich. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 46 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 1309 records from Ocean crust Targeted Locus (Loci). 406 records from PSUZC-Mammal Collection. 3 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 161 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 32 records from Three new species of Ochyrocera (Araneae, Ochyroceratidae) from Southeastern Brazil. 6219 records from Canadian National Collection of Insects. 2 records from First description of the female of the spider Savignia zero Eskov, 1988 (Araneae: Linyphiidae). 3 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 70 records from Distribution of hydropolyp species in surface sediments of the Red Sea (Table 5). 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 425 records from GCP_2017_12_18. 361 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 17754 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1419 records from (Table 6) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1018A sediments. 87 records from Gulf of Gdansk. 3067 records from Museu Paraense Emílio Goeldi - Diptera Collection. 853 records from Planktic foraminifera abundance of Hole 80-549A. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 30 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-101BX. 1364 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 146 records from Benthic foraminifera abundance of Hole 34-320. 60 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 52125 records from Herbarium Senckenbergianum (FR). 334 records from Loup 2008 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 276 records from DREAL Auvergne - Reptiles - 2015. 51674 records from Invertebrate Zoology Division, Yale Peabody Museum. 19947 records from Merseyside BioBank Active Naturalists (unverified). 24 records from Six new species of Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) with redescription of additional species and new distributional records. 350 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 523 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V23-82. 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 653 records from Ectomycorrhiza species on all VIP´s April 2008. 364 records from Pollen profile 1 from Richland Creek. 91016 records from CSU Chico – Chico State Herbarium - Vascular Plants. 1152 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 47 records from Planktic foraminifera counts of sediment core RC17-69. 146 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 17 records from Nachtinsekten am Muldenufer. 59 records from Planktic foraminifera abundance of Hole 73-520. 1242 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Ernst Krenkel" in 1992”. 2183 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 145 records from Gronau - auf der Suche nach dem Neunauge. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 116 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 1412 records from Nannofossil abundance of Hole 94-607. 122 records from Faunal assemblage of sediment core GS7603-8. 2081 records from Thrips (Thysanoptera) in Norway. 1 records from A new species of Homo from the Late Pleistocene of the Philippines. 69 records from Entdeckertour am Muldestausee 1/05. 1 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 1879 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 160 records from BIOTOPE_2017_12_18. 108 records from BIRDRACE Diesmal sehen wir mehr. 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 8 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 2 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 1346 records from Weevils of Poland. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 26 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 1763 records from Arachnida of Costa Rica (INBio). 376 records from Occurrence of some antimalarial plants from Cameroon. 3132 records from Ross A. Layberry, Collection. 24 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 201 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 119 records from Microfossil abundance of Hole 50-416A. 2 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 22 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 25 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 97 records from uncultured bacterium Targeted Locus (Loci). 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 247 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Données naturalistes d'Olivier VILLEPOUX. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 274 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 86 records from Antarctic Parborlasia corrugatus. 11837 records from NCSM Non-molluscan Invertebrates Collection. 106744 records from The AAU Herbarium Database. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 2 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 2752 records from Bird Monitoring 2017, Meise Botanic Garden. 5420 records from Colecção Entomológica do Museu de História Natural de Maputo. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 23 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 148 records from Collection Polychaeta - ZSRO. 19794 records from imr_mareano_rpsledge. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 171 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 1036 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 110 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 613 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 23 records from Abundance of benthos infauna at station GIK23055-1. 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 9 records from Benthic macrofauna abundance of sediment core 13200-017. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 1 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 528 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 2782 records from Gunma Museum of Natural History, Fungi Specimen. 297 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 2 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 14461 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 4 records from Kirchenforst. 252 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 26220 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 61 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 8 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 9597 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 1800 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 33 records from Nannofossil abundance of Hole 15-146A. 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 5 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 1554 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 297 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 160902 records from UWFC Ichthyology Collection. 279 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 58 records from Mamíferos laguna El Tinije. 5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 17701 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 11088 records from Données naturalistes d'Anthony TURPAUD. 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 512 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 558 records from Área Otún Quimbaya - Densidad poblacional valores objeto de conservación Santuario de Fauna y Flora Otún Quimbaya, 2016. 16 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 80678 records from CUMV Fish Collection. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 3 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 378 records from Tsetse flies of East Africa update. 2647 records from SPC CoFish Fish Observations Nauru 2005. 3680 records from Flora of Sumatra : Vascular plant collection from Batang Toru Forest deposited in ANDA Herbarium. 102 records from A Lichen Survey of the Ben Nevis Plateau. 2 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 19 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 2146 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 1075 records from tree climbing bryophytes & lichens at tree base and crown with traits. 526 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 310 records from Données naturalistes de Laurent PONCET. 16 records from Coccolith counts of multinet SO119_MSN1301. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 43819 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 5314 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 1 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 142 records from Planktic foraminifera abundance of Hole 32-313. 11107 records from Royal Ontario Museum Fungarium (TRTC). 159 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 45422 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 4686 records from Butterfly_conservation_2017_12_18. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 2 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 34211 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 14 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 3429 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 471 records from Benthic foraminifera counts of sediment core GIK23342-6. 547 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 11 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 99 records from Düne am Ulvenberg (Darmstadt). 2 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 3 records from Données naturalistes d'Emilie WEBER. 82328 records from Mammals housed at MHNG, Geneva. 2 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 339 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 2630 records from Swiss Psyllid (Hemiptera) Collections - Basel. 10 records from Sediment properties of core PLG95B_01BOXG. 414 records from Arctic sea-ice and sub-ice seawater raw sequence reads. 16 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 537 records from Pilotovervåking av dragehode Dracocephalum ruyschiana. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 1059 records from Planktic foraminifera abundance of Hole 15-148. 250 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 225 records from UWIZM Mantodea. 2 records from A new and five rare bdelloids from Korea. 535 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 12 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 17 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 4294 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 9 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil. 161 records from UNM Earth Sciences Collection (Arctos). 1590 records from Phenological Center - Plants (Murmansk). 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 10293 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 186 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 22 records from New records of ant species from Yunnan, China. 77 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 48 records from Survey of Plankton Diatoms in Nanren Lake. 3388 records from Caracterización biológica en la Serranía de San Lucas 2015. 1505 records from Great Koala Count 2. 2394 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 277 records from Nannofossil abundance of Hole 22-217. 1065 records from Bird specimens of Komatsu City Museum. 2 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 80 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 84 records from Total foraminifera counts of multinet M21/5_MSN728. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 135 records from Boreonemoral regnskog på østsiden av Lygrespollen. 4 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 6 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 26 records from Liste des oiseaux de BZM Belambo. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 50 records from Beetles on polypores at 4 sites in Norway. 72 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 98 records from Collection Crustacea - ZSRO. 1590 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 24 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 14 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 1259 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 93 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 2 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 76 records from BIRDRACE Rheinische Wasserrallen. 1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 901 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 2 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1576 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 173 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 2747 records from Données naturalistes de David HAPPE. 134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 18 records from Nannofossil abundance of Hole 3-18. 2 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2898 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 50 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 836 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 195 records from Pedestrian mammals census in W National Park. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 29741 records from BLS Rare and Threatened Lichen Records: England. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 427233 records from Israel Nature and Parks Authority. 85 records from Range table from benthic foraminifers in ODP Hole 171-1052A. 34 records from Sipuncula collection of National Museum of Nature and Science. 9871 records from Micro-moths distribution for Dumfries and Galloway. 194 records from Pottundkopp. 2588 records from Museo de Historia Natural, Colección de Vertebrados e Invertebrados - Colección de Mamíferos. 11285 records from Catálogo de insectos de la colección del Centro de Entomología. 5 records from Luciobarbus lanigarensis and L. numidiensis, two new species of barbels from the Mediterranean Sea basin in North Africa (Teostei: Cyprinidae). 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 1297 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 324 records from (Table 3) Occurrence of dinoflagellate cyst species in ODP Hole 113-696B. 1 records from Emeia gen. nov., a new genus of Luciolinae fireflies from China (Coleoptera: Lampyridae) with an unusual trilobite-like larva, and a redescription of the genus Curtos Motschulsky. 24 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 11 records from Nannofossil abundance of Hole 51-417B. 12 records from Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes- group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae). 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 4761 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 102 records from DAYO: Invasive Alien Reptiles in the Philippines. 242 records from MPM Herpetology. 11 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 26 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 4036 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 10 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 2 records from The Vietnamese population of Megophrys kuatunensis (Amphibia: Megophryidae) represents a new species of Asian horned frog from Vietnam and southern China. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 3968 records from Antarctic Jellyfish. 12 records from Occurrence of mammalia relicts at site Luttenberg. 363305 records from National Trust Species Records. 255219 records from Australian National Wildlife Collection provider for OZCAM. 6756 records from Diversité floristique des espèces menacées prioritaires du Bénin (Afrique de l'Ouest).. 253 records from Pukkellaks i Norge 2017. 2762 records from HUSC - Herbário Unisanta. 1 records from A new genus, Protaustrosimulium, for four species of Australian black flies (Diptera: Simuliidae). 10656 records from Crispin S. Guppy Collection. 1351 records from Copepoda associated with Caribbean reef-dwelling cnidarians, echinoderms and sponges. 74 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 63 records from Planktic foraminifera abundance of Hole 11-106B. 35 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 80 records from Données naturalistes d'Emmanuel ICARDO. 490 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 688 records from Algae, Norwegian College of Fishery Science. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 105 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1372. 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 2 records from A new shrimp species of the genus Lebbeus White, 1847 (Crustacea: Deacpoda: Caridea: Thoridae) from a deep-sea cold seep site off southwestern Taiwan. 2 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 1177859 records from Australian Museum provider for OZCAM. 136 records from Revision of the South African endemic bee genus Redivivoides Michener, 1981 (Hymenoptera: Apoidea: Melittidae). 1 records from 5. Wiener Gemeindebezirk. 27391344 records from Observation.org, Nature data from the Netherlands. 82 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 97 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 13 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 7448 records from Mammal records for Dumfries and Galloway. 471 records from Phytoplankton data collected from a diurnal station in Sevastopol Bay (Black Sea) during 1952. 42 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 34 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 7 records from Cytheroid ostracods (Crustacea) from South Korea, with description of a new species. 6 records from Occurrence of mammalia relicts at site Barova Cave. 180 records from osac_oarisma. 1 records from Minjerribah (Diptera: Dolichopodidae), a new genus from coastal Queensland, Australia. 319109 records from Vascular plant herbarium, Tromsø Museum. 70 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 183 records from Inventaire des Scléractiniaires de la région du Diahot. 36 records from Terre d'huiles. 91 records from BIRDRACE SchrägeVögel. 13716 records from NYSM Mammals. 98 records from Streuobstwiese Stedar 2008. 3 records from Lost species in Cameroon: rediscovery of the endangered freshwater crab, Louisea balssi (Bott, 1959) (Brachyura: Potamonautidae), with notes on its ecology and conservation. 141 records from Microfossil abundance of Hole 29-277. 4054 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 91 records from Cape Darnley Early-Autumn Phytoplankton Bloom, March 2012. 122 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 235 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 37419 records from JPB - Herbário Lauro Pires Xavier. 1502 records from Canadian Museum of Nature Fish Collection. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 18 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 12 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 1200 records from 2019_mjim_in. 18 records from Revision of Netomocera Bouček (Hymenoptera: Chalcidoidea: Pteromalidae), excluding the Oriental species. 3729 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 1814 records from Bats of Poland. 137 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 75 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 34 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 67553 records from Field Museum of Natural History (Botany) Bryophyte Collection. 11 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-083BX. 95 records from Observation des mammifères sur le territoire de la Métropole Rouen Normandie. 13344 records f
Keywords: GBIF; biodiversity; species occurrences